If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(7x + -6) + 1 = 42x + -35 Reorder the terms: 6(-6 + 7x) + 1 = 42x + -35 (-6 * 6 + 7x * 6) + 1 = 42x + -35 (-36 + 42x) + 1 = 42x + -35 Reorder the terms: -36 + 1 + 42x = 42x + -35 Combine like terms: -36 + 1 = -35 -35 + 42x = 42x + -35 Reorder the terms: -35 + 42x = -35 + 42x Add '35' to each side of the equation. -35 + 35 + 42x = -35 + 35 + 42x Combine like terms: -35 + 35 = 0 0 + 42x = -35 + 35 + 42x 42x = -35 + 35 + 42x Combine like terms: -35 + 35 = 0 42x = 0 + 42x 42x = 42x Add '-42x' to each side of the equation. 42x + -42x = 42x + -42x Combine like terms: 42x + -42x = 0 0 = 42x + -42x Combine like terms: 42x + -42x = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| -6x+8-4(x-1)=-(5x-5)-4x+4 | | 83.2=8(m+3.1) | | 5x+z+6=20 | | 2/3b=8/15 | | .08(y-5)+.06y=.04y-.03(10) | | 5(x+12)=150 | | 7x+8.96=3x+16 | | 1/4-8=6 | | 2(z+8)+16=4 | | 10+3t=-5 | | 2x-2y= 12 | | -[10x-(18x+1)]=1+(7x+10) | | 5/1/5 | | 3x^2+9=-3x | | 2x=5x-63 | | -5(x-5)-4=21 | | 2x-3(4-3x)=3(x-4)-32 | | 3x+49=5x+15 | | -5(6-r)=10 | | 2x+2=4x-80 | | 5x+12=-38-5 | | w(2w+1)=55 | | 4.25x=-46.25 | | 8.73x+1=76.2129+x | | -8x+(-5)=16 | | 12x-53=6x+25 | | -x-4=-2(x-2) | | 12x-53+6x+25=180 | | -8x+-5=16 | | 2x^2+33x=-45 | | 1/2(15)(13)sin57 | | 2x+30+13x+30=90 |